The future of novel diagnostics in medical mycology. Issue 4 (April 2015) - Teles, Fernando; Seixas, Jorge
Abstract : N/A: Several fungal diseases have become serious threats to human health and life, especially upon the advent of human immunodeficiency virus/AIDS epidemics and of other typical immunosuppressive conditions of modern life. Accordingly, the burden posed by these diseases and, concurrently, by intensive therapeutic regimens against these diseases has increased worldwide. Existing and available rapid tests for point‐of‐care diagnosis of important fungal diseases could enable the limitations of current laboratory methods for detection and identification of medically important fungi to be surpassed, both in low‐income countries and for first‐line diagnosis (screening) in richer countries. As with conventional diagnostic methods and devices, former immunodiagnostics have been challenged by molecular biology‐based platforms, as a way to enhance the sensitivity and shorten the assay time, thus enabling early and more accurate diagnosis. Most of these tests have been developed in‐house, without adequate validation and standardization. Another challenge has been the DNA extraction step, which is especially critical when dealing with fungi. In this paper, we have identified three major research trends in this field: (1) the application of newer biorecognition techniques, often applied in analytical chemistry; (2) the development of new materials with improved physico‐chemical properties; and (3) novel bioanalytical platforms, allowing fully automated testing. Keeping up to date with the fast technological advances registered in this field, primarily at the proof‐of‐concept level, is essential for wise assessment of those that are likely to be more cost effective and, as already observed for bacterial and viral pathogens, may provide leverage to the current tepid developmental status of novel and improved diagnostics for medical mycology.